Associated risk factors to non-compliance to methadone maintenance therapy - Musa, Ramli; Abu Bakar, Ahmad Zafri; Mohamed Rozali, Junid; Sidi, Hatta (Malaysian Medical Association, 2012)
The escalating problem of opiate dependence in Malaysia and the limitations of regimental approach of forced admission to rehabilitation centres had triggered the government to expand the methadone maintenance therapy to become a national programme. This study aimed to evaluate the short-term outcomes of the Methadone Maintenance Therapy programme in one of the busiest hospital in east coast Malaysia. We also explored the prevalence on non-compliance and factors associated to it. A total of 172 patient case notes at Methadone Clinic Hospital Tengku Ampuan Afzan (HTAA) were retrieved for relevant data. A short survey was also conducted to determine the subjects’ current employment and marital status. The programme’s retention rate was 62% and factors associated with poor compliance were unemployment, low quality of life scores and low dose of methadone. A special attention on the patients with these three risk factors may improve their compliance to MMT. The short-term evaluation of MMT at HTAA revealed favourable findings.